Perancangan Aplikasi Perangkingan Perguruan Tinggi Menggunakan Fuzzy Simple Additive Weighting (SAW) (Studi Kasus: 25 PT Wilayah Kopertis XIII Provinsi Aceh) - Rizaldi Akbar (KITA Institute, 2018)
This research aims to make a ranking College in Aceh and its applications processing data.The College in question is 25 (twenty five) in the region XIII Kopertis Aceh province using Simple Additive Weighting (SAW) is one method that can be used to solve the problem of Fuzzy MADM. Application of decision support system (DSS) this can take account of all criteria that support decision making in order to help speed up and facilitate the decision-making process and do the rangking in particular. Based on the results of the study it can be concluded then the Fuzzy method of Multi Attribute Decision Making (FMADM) and Simple Additive Weighting (SAW) can provide information ranking College, where the final results will be calculated the value of preferences (Vi) the highest of each alternative.The highest value was made the first priority as the best college. The end result of the application of the method of College ranking in the form of the SAW with the first order at Serambi Mekkah of University with the value of 0.89 and a low of STMIK Abulyatama value of 0.38.